2006
DOI: 10.3386/w12386
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Inheritance Receipt on Retirement

Abstract: Abstract:This paper provides new evidence on how wealth shocks influence retirement behavior.Economic theory generally posits that leisure is a normal good, yet it is difficult to obtain reliable empirical estimates of the wealth effect because wealth is correlated with numerous unobservable characteristics that affect labor supply. We use inheritance receipt as a wealth shock, and find that it is associated with a significant increase in the probability of retirement, especially when the inheritance is unexpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
58
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 6 publications
7
58
1
Order By: Relevance
“…A similar correlation between inheritance and retirement was found in a study by Brown et al (2010). This observation might reflect international differences in the prevalence of heirs and in retirement ages (Table A2).…”
Section: The Datasupporting
confidence: 85%
“…A similar correlation between inheritance and retirement was found in a study by Brown et al (2010). This observation might reflect international differences in the prevalence of heirs and in retirement ages (Table A2).…”
Section: The Datasupporting
confidence: 85%
“…However, the implied responses are quantitatively smaller. 64 There is a literature studying the effects of inheritances on labor supply (e.g., Holtz-Eakin et al 1993;Brown et al 2010;Elinder et al 2012;Bø et al 2016). These studies generally find that inheritances lead to reductions in labor income and earnings as well as increased probability of retirement.…”
mentioning
confidence: 99%
“…Brown et al [11] provide new evidence on how wealth shocks influence retirement behaviour; inheritance is associated with a significant increase of the probability of retirement. Bloeman [12] empirically analyzed the effect of wealth on the retirement and concluded that there is a positive effect of wealth on early retirement.…”
Section: Introductionmentioning
confidence: 99%